Molybdenum-Cofactor Deficiency and Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The clinical, biochemical, and neuropathological findings in two neonates with molybdenum-cofactor deficiency presenting with convulsions are reported from the Academic Medical Center, Amsterdam, The Netherlands.